ANALISIS PENGARUH GENDER, MOTIVASI, DAN LITERASI KEUANGAN PADA SANDWICH GENERATION TERHADAP INTENSI BERINVESTASI - Yenny Ernitawati; Gian Fitralisma (Jurnal Proaksi, 2021)
This study aims to analyze the effect of gender, motivation, on intention to invest UMKM. The dependent variable is intention to invest, the independent variable is gender and motivation. The population is all productive woman. Sampling in this study used purposive sampling technique. Valid sample of 181 was recruited in this study, and participants voluntarily answered online questionnaires. The analytical technique used is a structural equation model with the IBM Statistical Package for the Social Sciences version 25 application. The results show a significant positive effect between motivational variables and financial literacy on investment intentions. And the gender variable has no effect on investment intentions.). Keywords: Gender, Motivation,financial literacy, investment intentions